Trabajo de mejora del almacén en una empresa comercializadora de equipos industriales: APTEIN S.A.C. - Lara Tiravanti, Claudia Verónica (2020)
This thesis is focused on the analysis and evaluation of the warehouse system of an industrial equipment trading company to apply an improvement. The objective is to propose methodologies that allow to administrate the warehouse in a more efficient way. The chosen alternatives seek to increase the productivity, though defining and documented working methods, in the internal processes of reception, movement and assembly, as well as the decrease of the duty cycles time thanks to a better layout distribution. To accomplish what is mention before, this thesis has used several tools that are known used in industrial engineering area, such as: Ishikawa diagram, Klein factorial, comparison boards ,5S methodology, etc. These tools are going to allow us to make an evaluation, diagnosis and provide the solution that best suits the needs of the company. The thesis is composed by six chapters, the three first make a reference to the description of the company and the evaluation of the internal and external environments, in order to review their strengths, weaknesses, opportunities and threats. The subsequent three chapters, will develop the solutions found and establish the action plan. It is worth mentioning that this thesis’ scope only includes what was mentioned on the previous paragraphs, it does not include the implementation of the Project itself because it will depend on the company’s decision.